2020
DOI: 10.21037/atm-19-2756
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus (HPV) profiles in breast cancer: future management

Abstract: Breast cancer (BC) is frequent among women in worldwide as well as in India. Several studies have reported a wide variation (1.6-86.2%) in the frequency of incidence of human papillomavirus (HPV) infection in BC with high prevalence of high risk HPV16 subtype. HPV infection in breast can occur through different routes like body fluid or by micro-lesion of breast skin from genital/agential sites, though the actual mode of HPV transmission is not yet known in details. Frequent integration and sequence variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 96 publications
2
27
0
7
Order By: Relevance
“…Human papillomavirus and EBV can co-exist and cooperate in human cancers, especially breast cancer (32). The prevalence of HPV in breast cancer varies widely from 1.6 to 86.2% among countries around the world (33). This rate in Iran has been reported in various studies from 6.7 to 40.5%, which is considered to be 23.7% on average (34).…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus and EBV can co-exist and cooperate in human cancers, especially breast cancer (32). The prevalence of HPV in breast cancer varies widely from 1.6 to 86.2% among countries around the world (33). This rate in Iran has been reported in various studies from 6.7 to 40.5%, which is considered to be 23.7% on average (34).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of HPV infection was reported in BC samples from women with HPV-associated SILs [ 77 , 78 ]. Taken together, these findings allowed the authors to suggest that HPV could reach the breast tissue through circulation (blood or lymphatic systems) in patients who displayed HPV-positive cervical cancer [ 79 ]. Bodaghi S et al (2005) and others suggested that HPV could be transmitted through the bloodstream because HPV DNA was found in peripheral blood mononuclear cells (PBMC) [ 80 ].…”
Section: Hpv Infection and Breast Cancermentioning
confidence: 99%
“…However, further studies are needed to clarify whether HPV DNA is transported from HPV infected sites, through EV, to this anatomical site. Another theory proposes that HPV could reach the breast tissue through nipple or areola microlesions of breast skin that may occur during oral-breast or genital-breast sexual intercourse [ 79 ]. Therefore, considering that HPV infection requires direct contact with cutaneous or mucosal epithelium, this transmission route to the breast appears to be the most feasible alternative for HPV entry to breast cells.…”
Section: Hpv Infection and Breast Cancermentioning
confidence: 99%
“…En la medida en que se ha descubierto la relevancia de los VPH-AR en el desarrollo de carcinomas anogenitales y orofaríngeos, se han empezado a investigar y detectar la presencia de estos virus, principalmente los genotipos 16 y 18, en una variedad de neoplasias malignas donde no se tenía conocimiento previo de la asociación con este virus. Ejemplo de esto son algunos carcinomas de pulmón [10], carcinomas gastrointestinales [11], esofágicos [12] y carcinomas de mama [14,15]. Se han teorizado diferentes hipótesis de cómo actúa este virus en la oncogénesis de estas neoplasias, tradicionalmente asociadas a otros factores de riesgo, como infecciones, específicamente la infección por Helicobacter pylori en el adenocarcinoma gástrico de tipo intestinal, o asociadas a características relacionadas con el estilo de vida, como el tabaquismo y la obesidad, en el carcinoma de pulmón y en el de mama, respectivamente.…”
Section: Laboratorio Molecular En Virus Del Papiloma Humano (Vph) Y Cáncer Molecular Laboratory In Human Papillomavirus (Hpv) and Cancerunclassified
“…Se han teorizado diferentes hipótesis de cómo actúa este virus en la oncogénesis de estas neoplasias, tradicionalmente asociadas a otros factores de riesgo, como infecciones, específicamente la infección por Helicobacter pylori en el adenocarcinoma gástrico de tipo intestinal, o asociadas a características relacionadas con el estilo de vida, como el tabaquismo y la obesidad, en el carcinoma de pulmón y en el de mama, respectivamente. Al parecer el papel que juegan los VPH-AR guarda relación con su capacidad oncogénica, al alterar el proceso de apoptosis y estimular la proliferación celular descontrolada, secundaria en gran medida a la actividad de los oncogenes E6 y E7 [10][11][12][13][14].…”
Section: Laboratorio Molecular En Virus Del Papiloma Humano (Vph) Y Cáncer Molecular Laboratory In Human Papillomavirus (Hpv) and Cancerunclassified